2017
DOI: 10.1016/j.yjmcc.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of succinate and ROS in reperfusion injury – A critical appraisal

Abstract: We critically assess the proposal that succinate-fuelled reverse electron flow (REF) drives mitochondrial matrix superoxide production from Complex I early in reperfusion, thus acting as a key mediator of ischemia/reperfusion (IR) injury. Real-time surface fluorescence measurements of NAD(P)H and flavoprotein redox state suggest that conditions are unfavourable for REF during early reperfusion. Furthermore, rapid loss of succinate accumulated during ischemia can be explained by its efflux rather than oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 201 publications
(329 reference statements)
5
112
0
1
Order By: Relevance
“…However, TRAP1 also limits ROS generation from the respiratory chain SDH/complex II, thereby increasing the Ca 2+ threshold required for mPTP opening in cancer cells, protecting them from death stimuli . High Ca 2+ loads (approximately 50 nmol Ca 2+ /mg protein or higher concentrations, depending on the oxidizable substrate) into mitochondria are critically involved along with ROS as triggers for activation of the mPTP and cell death induction (Figure ) . However, it has not been elucidated exactly how the mitochondrial Ca 2+ (mCa 2+ ) overload triggers cell death.…”
Section: Relationship Of Redox Control Ca2+/ros Triggering To the MImentioning
confidence: 99%
See 3 more Smart Citations
“…However, TRAP1 also limits ROS generation from the respiratory chain SDH/complex II, thereby increasing the Ca 2+ threshold required for mPTP opening in cancer cells, protecting them from death stimuli . High Ca 2+ loads (approximately 50 nmol Ca 2+ /mg protein or higher concentrations, depending on the oxidizable substrate) into mitochondria are critically involved along with ROS as triggers for activation of the mPTP and cell death induction (Figure ) . However, it has not been elucidated exactly how the mitochondrial Ca 2+ (mCa 2+ ) overload triggers cell death.…”
Section: Relationship Of Redox Control Ca2+/ros Triggering To the MImentioning
confidence: 99%
“…Together, these data show that the mitochondrial respiratory response and the kinetics of ΔΨ m loss from mPTP opening will vary depending on metabolic substrate availability. In marked contrast, in another study with isolated heart mitochondria, it was shown that the presence of succinate (with no addition of rotenone) provided resistance to the mPTP opening induced by Ca 2+ loads and despite promoting increased rates of ROS production (as compared with glutamate + malate as the oxidizable substrates). Further, once mPTP opening occurred, the mitochondria produced much more ROS in the presence of succinate.…”
Section: Relationship Of Redox Control Ca2+/ros Triggering To the MImentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a ROS-responsive nanoparticle drug-delivery system offers a promising approach for the treatment of various I/R injuries such as stroke and renal infarction. [20] Conjugation of ROS-responsive nanoparticles to an MRI tracer such as gadolinium or to a radiotracer for PET imaging holds great promise for utilizing ROS-responsive nanoparticles for diagnosis of MI and in vivo assessment of ROS levels. [14][15][16][17][18] Therefore, ROS-responsive nanoparticles may also represent a promising strategy for targeted drug delivery in the treatment of a number of diseases in addition to I/R injury.…”
mentioning
confidence: 99%